Transcatheter aortic valve implantation in the presence of hematologic malignancies - Cenk Sarı; Hüseyin Ayhan; Serdal Baştuğ; Hacı Ahmet Kasapkara; Bilge Duman Karaduman; Abdullah Nabi Aslan; Mehmet Burak Özen; Emine Bilen; Nihal Akar Bayram; Telat Keleş; Tahir Durmaz; Engin Bozkurt (KARE Publishing, 2015)
OBJECTIVE: Cardiac surgery may be performed in patients with hematologic disorders, but carries an increased risk of morbidity. This series describes an experience of transcatheter aortic valve implantation (TAVI) in patients with hematologic malignancies, and highlights the technical considerations to be kept in mind. METHODS: Between June 2011 and April 2014, 133 consecutive high-risk patients with symptomatic severe aortic stenosis were treated with TAVI at our centre. Based on consensus among the local heart team, five patients with hematologic malignancies (myelodysplastic syndrome [2],chronic lymphocytic leukemia [2], Hodgkin lymphoma [1]) were considered high risk for surgery (Logistic EUROSCORE 17.2+-14.0% and STS score 5.8+-4.3%). Serial echocardiographic and clinical follow-ups were done pre- and post-procedure, at discharge, and at 1, 3, 6 and 12 months. RESULTS: Our procedural success rate was 80%. Two heart valves were implanted in one patient due to aortic embolization of the previous valve. Perforation of the right ventricle and cardiac tamponade occurred in the same patient. Mean blood transfusion requirement was 1.0+-1.4 U (range: 0 to 3 U). Mean aortic valve gradient was reduced from baseline to 9.2+-3.27 mmHg, and the effective orifice area was significantly increased to 1.96+-0.29 cm2. Paravalvular aortic regurgitation (AR) was absent-mild in all the patients. CONCLUSION: This present series demonstrates that TAVI with a balloon-expandable valve can be performed safely and effectively and is technically feasible in high-risk patients with hematologic malignancies.